Permitted delation: dignity of the human person and the rights of personality - Soares, Marcelo Negri (2023)
Since ancient times, history has shown us an example of betrayal, which is also ancient. Judas Iscariot was a biblical character responsible for the betrayal of Jesus Christ. Over the years it can be said of an evolution and a modernization of criminality, a true involution of man. Then, in this hiatus, the winning complaint appears, a mechanism that makes it possible to obtain information for criminal elucidation. Although it is a cause for disagreements in the legal environment, especially when it comes to human dignity, it is a necessary tool in the face of the increasingly elaborate articulations of criminal organizations in the country. This benefit is provided for in several Brazilian laws: Penal Code, Laws n. 8.072/90 - Hideous and similar crimes, L. 9.034/95 - Criminal organizations, L. 7.492/86 - Crimes against the national financial system, L. 8.137/90 - Crimes against order tax, economic and against consumer relations, L. 9.613/98 - Money laundering, L. 9.807/99 - Witness protection, L. 8.884/94 - Offenses against the economic order and L. 11.343/06 - Drugs and the like. Thus, the present work, based on the hypothetical-deductive method, has as its main objective to elucidate the legal nature of this institute, the debate around its effectiveness and to outline the main innovations recently introduced.